Two-component polyurethane adhesive and use method thereof

Through the design of two-component polyurethane adhesive, the addition reaction between components A and components B is used to solve the problems of slow curing speed, insufficient bonding strength and poor aging resistance in the bonding of plastics and composites, and the effect of high strength, toughness and aging resistance is achieved, and solvent residue is reduced.

CN119799262APending Publication Date: 2025-04-11湖北回天新材料(宜城)有限公司 +3
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411990722.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the structural bonding of plastics and composite materials, existing adhesives have problems such as slow curing speed, insufficient bonding strength, poor aging resistance and a lot of solvent residues.

Method used

A two-component polyurethane adhesive is provided, by separating component A and component B, wherein component A contains hydroxy compounds and other additives, and component B contains isocyanate-terminated polyurethane prepolymers and other additives, both undergo an addition reaction during use, achieving adhesiveness and increasing bond strength.

Benefits of technology

It achieves balance and balance between high strength and high toughness, long opening time, fast curing at high temperature, reducing solvent residue, and excellent aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223590740000051
    Figure BDA0005223590740000051
  • Figure BDA0005223590740000061
    Figure BDA0005223590740000061
  • Figure BDA0005223590740000062
    Figure BDA0005223590740000062
Patent Text Reader

Abstract

The invention discloses a two-component polyurethane adhesive and a use method thereof, and relates to the technical field of adhesives. Comprising a component A and a component B which are separately arranged, wherein the component A comprises a hydroxyl-containing compound, a chain extender, a catalyst, an anti-aging agent, an anti-hydrolysis agent, a filler, a moisture scavenger and a thixotropic agent; the component B comprises an isocyanate-terminated polyurethane prepolymer, isocyanate, a water removal agent, a silane coupling agent, a plasticizer, a filler and a thixotropic agent; the hydroxyl-containing compound comprises hydroxyl-terminated polybutadiene and a first hydroxyl-containing compound. The composite material has the advantages of long opening time, fast curing at high temperature, high body strength, high shear strength and high elongation at break, and realizes consideration and balance of high strength and high toughness. Meanwhile, the bi-component polyurethane adhesive disclosed by the invention does not contain a solvent, so that the solvent residue is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of adhesives, and in particular to a two-component polyurethane adhesive and a method for using the same. Background Art

[0002] Structural adhesives refer to adhesives that are used in bonding load-bearing structural parts, can withstand large dynamic loads, static loads and can be used for a long time. Structural adhesives are increasingly replacing bolts, rivets, welding and other forms to achieve effective connection of metals, plastics, etc. Structural adhesives can be mainly divided into cyclic resin structural adhesives, acrylate structural adhesives and polyurethane structural adhesives according to the type of matrix resin. Epoxy resin structural adhesives are hard and brittle, with poor toughness; acrylate structural adhesives have a strong odor, irritate the respiratory tract, and are not good for human health. Polyurethane structural adhesives, especially solvent-free polyurethane structural adhesives, are safe and environmentally friendly, with adjustable curing speed and strength, and have excellent adhesion, flexibility, low temperature resistance and other properties, and have been widely used.

[0003] The lightweighting of automobiles means reducing the curb weight of automobiles as much as possible while ensuring the strength and safety performance of automobiles, thereby improving the power of automobiles, reducing fuel consumption, and reducing exhaust pollution. Experiments have shown that when the weight of automobiles is reduced, fuel consumption will also be reduced. Due to the needs of environmental protection and energy saving, the lightweighting of automobiles has become a trend in the development of automobiles in the world. With the advancement of lightweighting of automobiles, the materials of automobile tailgates have developed from traditional steel tailgates to composite tailgates and then to all-plastic tailgates.

[0004] Traditional connection technologies, such as welding and riveting, have the disadvantage of adding extra weight to the vehicle body when used to connect dissimilar materials and non-metallic materials. Adhesive technology with excellent mechanical and weight-reducing properties is one of the effective ways to achieve the connection between dissimilar materials and non-metallic materials. The adhesives currently on the market still have problems such as slow curing speed, insufficient bonding strength, poor aging resistance, and high solvent residue for structural bonding of plastics and composite materials, especially plastics and composite materials with low surface energy. Summary of the invention

[0005] The present application provides a two-component polyurethane adhesive and a method for using the same to solve the existing problems of slow curing speed, insufficient bonding strength, poor aging resistance, and solvent residue.

[0006] In a first aspect, the present application provides a two-component polyurethane adhesive, comprising a component A and a component B which are separately arranged, wherein:

[0007] Component A includes: hydroxyl-containing compounds, chain extenders, catalysts, anti-aging agents, anti-hydrolysis agents, fillers, dehumidifiers and thixotropic agents;

[0008] Component B includes: isocyanate-terminated polyurethane prepolymer, isocyanate, water scavenger, silane coupling agent, plasticizer, filler and thixotropic agent;

[0009] The hydroxyl-containing compound includes hydroxyl-terminated polybutadiene and a first hydroxyl-containing compound.

[0010] The present application sets up separately arranged component A and component B, wherein the hydroxyl group in component A and the isocyanate group in component B undergo addition reaction when used, thereby achieving adhesion and improving bonding strength, while the polar groups in component A and component B can achieve reliable bonding with the substrate. It also has a long open time, can be quickly cured at high temperatures, has high bulk strength, high shear strength, and high elongation at break, achieving a balance between high strength and high toughness. At the same time, the two-component polyurethane adhesive of the present application does not contain solvents, reducing solvent residues.

[0011] In some embodiments, the hydroxyl value of the hydroxyl-terminated polybutadiene is 20 mg to 150 mg KOH / g, where the hydroxyl value refers to the number of milligrams of potassium hydroxide equivalent to the hydroxyl groups in 1 g of the sample. When the hydroxyl value of the hydroxyl-terminated polybutadiene is within this range, the cured product can have excellent mechanical properties, hydrolysis resistance, electrical insulation, acid and alkali resistance, aging resistance and adhesion properties; and / or,

[0012] The number average molecular weight of the hydroxyl-terminated polybutadiene is 1000 to 8000, and the number average molecular weight of the hydroxyl-terminated polybutadiene refers to the molecular weight obtained by weighted average of the number of molecules of different molecular weight components in the polymer material. The number average molecular weight of the hydroxyl-terminated polybutadiene is within this range, so that the cured product can have excellent mechanical properties, hydrolysis resistance, electrical insulation, acid and alkali resistance, aging resistance and adhesion properties.

[0013] In some embodiments, the molecular weight of the first hydroxyl-containing compound is 100 to 1000. Within this range, the strength of the cured product can be increased while enhancing toughness. The amount of hydroxyl groups in the first hydroxyl-containing compound can be 100 mg to 500 mg KOH / g.

[0014] In some embodiments, the first hydroxyl-containing compound includes at least one of diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, ethylene glycol tert-butyl ether, propylene glycol methyl ether, dodecanol, sorbitol, glycerol and 2-ethyl-1,3-hexanediol. The use of at least one of the first hydroxyl-containing compounds can improve the strength of the cured product while enhancing the toughness; and / or,

[0015] The chain extender includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, methyl propylene glycol, dipropylene glycol and trimethylolpropane. By using at least one of the above chain extenders, linear polymers can be generated through chain extension reaction and a cross-linked network structure of polyurethane can be generated to improve strength; and / or,

[0016] The catalyst includes at least one of an organic metal compound and an amine compound. The main function of the catalyst is to shorten the reaction time and improve production efficiency. Using at least one of an organic metal compound and an amine compound can improve catalytic activity and reduce costs. The organic metal compound can be at least one of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate. The amine compound can be at least one of triethylenediamine, N,N-dimethylcyclohexylamine, triethanolamine, and N,N-dimethylethanolamine; and / or,

[0017] The anti-aging agent includes at least one of an ultraviolet absorber, a hindered amine light stabilizer, an anti-yellowing agent, an antioxidant and a bactericidal and mildew-proof agent. The use of an anti-aging agent can inhibit degradation and extend the service life of the material. The ultraviolet absorber can be at least one of UV-1, UV-320, UV-326 and UV-1130. The hindered amine light stabilizer can be at least one of light stabilizer 292, light stabilizer 622, light stabilizer 770 and light stabilizer 944. The anti-yellowing agent can be at least one of UDT, HN-130, SAS and XHTS-011. The antioxidant can be at least one of antioxidant 1010, antioxidant 1035, antioxidant 1036 and antioxidant 1076. The bactericidal and mildew-proof agent can be at least one of BBIT, OIT, BIT, SPT and DMDMH; and / or,

[0018] The anti-hydrolysis agent includes at least one of monocarbodiimide and polycarbodiimide, and the anti-hydrolysis agent can inhibit hydrolysis and alleviate hydrolysis. The monocarbodiimide can be at least one of Stabaxol I, Eustab HS-700, and Hycasyl 100, and the polycarbodiimide can be at least one of Stabaxol P, Stabaxol P100, and Stabilizer 9000; and / or,

[0019] The filler includes at least one of calcium carbonate, kaolin, wollastonite powder, talc, mica powder, titanium dioxide, silica powder, alumina, aluminum hydroxide, barium sulfate and calcium sulfate. The filler is used to reduce the production cost of the product and improve the hardness or other properties such as flame retardancy, reinforcement, heat resistance, etc.; and / or,

[0020] The dehydrating agent includes at least one of activated molecular sieve, vinyl trimethoxysilane and oxazolidine dehydrating agent, and the dehydrating agent is used to remove water in the system, reduce the occurrence of side reactions, and extend the shelf life of the product; and / or,

[0021] The thixotropic agent includes at least one of fumed silica and organic bentonite. The functions of the thixotropic agent mainly include thickening thixotropy, reinforcement, anti-sagging and anti-settling. The thixotropic agent significantly improves the mechanical properties, construction convenience and storage stability of the adhesive through its unique physical and chemical properties; and / or,

[0022] The plasticizer includes one or more of phthalic acid diester, adipate diester, sebacic acid diester, and phosphate ester, specifically at least one of dioctyl phthalate, dibutyl phthalate, diisononyl phthalate, dimethyl adipate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, tricresyl phosphate, and trioctyl phosphate. The plasticizer has the functions of adjusting viscosity and fluidity, improving flexibility and ductility, increasing adhesion and bonding strength, adjusting hardness and temperature resistance, and improving brittleness and impact resistance; and / or,

[0023] The isocyanate comprises at least one of toluene diisocyanate, diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, p-phenylene diisocyanate, 1,4-cyclohexane diisocyanate, xylylene diisocyanate, cyclohexane dimethylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate and polymethylene polyphenyl polyisocyanate, and the isocyanate is used as a curing agent, reacts with hydroxyl groups to form carbamate, undergoes a cross-linking reaction, and produces a cured product; and / or,

[0024] The silane coupling agent includes at least one of γ-glycidyloxypropyltrimethoxysilane, methyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, anilinemethyltriethoxysilane, anilinepropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The silane coupling agent plays a role in enhancing the wettability and substrate adhesion of the polyurethane adhesive.

[0025] In some embodiments, the viscosity of the isocyanate-terminated polyurethane prepolymer at 80° C. is 400 mPa·s to 1000 mPa·s. When the viscosity of the isocyanate-terminated polyurethane prepolymer at 80° C. is within this range, it can have better fluidity and processing performance.

[0026] In some embodiments, the isocyanate-terminated polyurethane prepolymer is prepared by the following method:

[0027] The hydroxy-terminated polybutadiene and the first part of the plasticizer are mixed and dehydrated to obtain a first product;

[0028] The first product is mixed with isocyanate and a second portion of plasticizer to react to obtain an isocyanate-terminated polyurethane prepolymer.

[0029] By first reacting the hydroxy-terminated polybutadiene with the first part of the plasticizer, and then reacting with the isocyanate and the second part of the plasticizer after dehydration, an isocyanate-terminated polyurethane prepolymer is obtained, which can make the polyurethane prepolymer have a higher qualified rate. The plasticizer reacts step by step, and the second part of the plasticizer can bring the residual isocyanate with a larger viscosity into the reactor, so that the product qualified rate is higher. It should be noted that the plasticizer and isocyanate here are included in the isocyanate-terminated polyurethane prepolymer, and are not included in the B component plasticizer and the isocyanate.

[0030] In some embodiments, the mass ratio of the first part of the plasticizer to the second part of the plasticizer is (4-9):1. When the mass ratio of the first part of the plasticizer to the second part of the plasticizer is within this range, the influence of the water in the second part of the plasticizer on the system can be reduced; and / or,

[0031] The water content of the first product is less than 500 ppm. When the water content of the first product is within this range, the reaction between the water in the system and the NCO in the system can be minimized; and / or,

[0032] The reaction temperature of mixing the first product with isocyanate and the second part of plasticizer is 70°C to 90°C, and the reaction time is 1 to 2 hours. The reaction temperature of mixing the first product with isocyanate and the second part of plasticizer is within this range, which can reduce the occurrence of side reactions.

[0033] In some embodiments, component A further comprises a pigment, wherein the pigment comprises at least one of carbon black, iron black and aniline black. Adding the pigment can distinguish components A and B, and using a black pigment can highlight the glue line in a light-colored substrate or hide the glue line in a dark-colored substrate.

[0034] In some embodiments, by weight:

[0035] Component A includes:

[0036]

[0037]

[0038] Component B includes:

[0039]

[0040] When the mass fraction of each substance in component A is within this range, the role of each raw material can be brought into play and the designed performance can be achieved.

[0041] When the mass fraction of each substance in component B is within this range, the role of each raw material can be brought into play and the designed performance can be achieved.

[0042] In a second aspect, the present application provides a method for using a two-component polyurethane adhesive, wherein component A and component B are mixed in a volume ratio of 1:1. Component A and component B are mixed in a volume ratio of 1:1 to bring into play the role of each raw material and achieve the designed performance. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0044] Structural adhesives are adhesives used in bonding load-bearing structural parts, which can withstand large dynamic and static loads and can be used for a long time. Structural adhesives are increasingly replacing bolts, rivets, welding and other forms to achieve effective connection of metals, plastics, etc.

[0045] Structural adhesives can be mainly divided into epoxy resin structural adhesives, acrylate structural adhesives and polyurethane structural adhesives according to the type of base resin. Epoxy resin structural adhesives are hard and brittle with poor toughness; acrylate structural adhesives have a strong odor, irritate the respiratory tract, and are not good for human health. Polyurethane structural adhesives, especially solvent-free polyurethane structural adhesives, are safe and environmentally friendly, with adjustable curing speed and strength, and have excellent adhesion, flexibility, low temperature resistance and other properties, and have been widely used.

[0046] The lightweighting of automobiles means reducing the curb weight of automobiles as much as possible while ensuring the strength and safety performance of automobiles, thereby improving the power of automobiles, reducing fuel consumption, and reducing exhaust pollution. Experiments have shown that when the weight of automobiles is reduced, fuel consumption will also be reduced. Due to the needs of environmental protection and energy saving, the lightweighting of automobiles has become a trend in the development of automobiles in the world. With the advancement of lightweighting of automobiles, the materials of automobile tailgates have developed from traditional steel tailgates to composite tailgates and then to all-plastic tailgates.

[0047] Traditional connection technologies, such as welding and riveting, have the disadvantage of adding extra weight to the vehicle body when used to connect dissimilar materials and non-metallic materials. Adhesive technology with excellent mechanical and weight-reducing properties is one of the effective ways to achieve the connection between dissimilar materials and non-metallic materials. The adhesives currently on the market still have problems such as slow curing speed, insufficient bonding strength, poor aging resistance, and high solvent residue for structural bonding of plastics and composite materials, especially plastics and composite materials with low surface energy.

[0048] In view of this, the present application provides a two-component polyurethane adhesive and a method of using the same to solve the existing problems of slow curing speed, insufficient bonding strength, poor aging resistance, and high solvent residue.

[0049] In a first aspect, the present application provides a two-component polyurethane adhesive, comprising a component A and a component B which are separately arranged, wherein:

[0050] Component A includes: hydroxyl-containing compounds, chain extenders, catalysts, anti-aging agents, anti-hydrolysis agents, fillers, dehumidifiers and thixotropic agents;

[0051] Component B includes: isocyanate-terminated polyurethane prepolymer, isocyanate, water scavenger, silane coupling agent, plasticizer, filler and thixotropic agent;

[0052] The hydroxyl-containing compound includes hydroxyl-terminated polybutadiene and a first hydroxyl-containing compound.

[0053] The present application sets up separately arranged component A and component B, wherein the hydroxyl group in component A and the isocyanate group in component B undergo addition reaction when used, thereby achieving adhesion and improving bonding strength, while the polar groups in component A and component B can achieve reliable bonding with the substrate. It also has a long open time, can be quickly cured at high temperatures, has high bulk strength, high shear strength, and high elongation at break, achieving a balance between high strength and high toughness. At the same time, the two-component polyurethane adhesive of the present application does not contain solvents, reducing solvent residues.

[0054] In combination with the first aspect, in some embodiments provided in the present application, the hydroxyl value of the terminal hydroxyl polybutadiene is 20 mg to 150 mg KOH / g, where the hydroxyl value refers to the number of milligrams of potassium hydroxide equivalent to the hydroxyl groups in 1 g of the sample. The hydroxyl value of the terminal hydroxyl polybutadiene is within this range, so that the cured product can have excellent mechanical properties, hydrolysis resistance, electrical insulation, acid and alkali resistance, aging resistance and adhesion properties.

[0055] In combination with the first aspect, in some embodiments provided in the present application, the number average molecular weight of the terminal hydroxyl polybutadiene is 1000 to 8000, and the number average molecular weight of the terminal hydroxyl polybutadiene refers to the molecular weight obtained by weighted average of the number of molecules of different molecular weight components in the polymer material. The number average molecular weight of the terminal hydroxyl polybutadiene is within this range, so that the cured product can have excellent mechanical properties, hydrolysis resistance, electrical insulation, acid and alkali resistance, aging resistance and adhesion properties.

[0056] In combination with the first aspect, in some embodiments provided in the present application, the molecular weight of the first hydroxyl-containing compound is 100 to 1000. Within this range, the strength of the cured product can be improved while enhancing toughness. The number of hydroxyl groups in the first hydroxyl-containing compound can be 100 mg to 500 mg KOH / g. Preferably, the molecular weight of the first hydroxyl-containing compound is 100 to 200. Within this range, the strength of the cured product can be further improved while enhancing toughness.

[0057] In combination with the first aspect, in some embodiments provided in the present application, the first hydroxy-containing compound includes at least one of diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, ethylene glycol tert-butyl ether, propylene glycol methyl ether, dodecanol, sorbitol, glycerol and 2-ethyl-1,3-hexanediol. The use of at least one of the above-mentioned first hydroxy-containing compounds can improve the strength of the cured product while enhancing the toughness.

[0058] In combination with the first aspect, in some embodiments provided in the present application, the chain extender includes at least one of ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, methyl propanediol, dipropylene glycol and trimethylolpropane. By using at least one of the above chain extenders, linear polymers can be generated through chain extension reactions and a cross-linked network structure of polyurethane can be produced to improve strength.

[0059] In combination with the first aspect, in some embodiments provided in the present application, the catalyst includes at least one of an organic metal compound and an amine compound, and the main function of the catalyst is to shorten the reaction time and improve production efficiency. The use of at least one of an organic metal compound and an amine compound can improve catalytic activity and reduce costs. The organic metal compound can be at least one of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate. The amine compound can be at least one of triethylenediamine, N,N-dimethylcyclohexylamine, triethanolamine, and N,N-dimethylethanolamine.

[0060] In combination with the first aspect, in some embodiments provided in the present application, the anti-aging agent includes at least one of an ultraviolet absorber, a hindered amine light stabilizer, an anti-yellowing agent, an antioxidant, and a bactericidal and mildew-proof agent. The use of an anti-aging agent can inhibit degradation and extend the service life of the material. The ultraviolet absorber can be at least one of UV-1, UV-320, UV-326, and UV-1130. The hindered amine light stabilizer can be at least one of light stabilizer 292, light stabilizer 622, light stabilizer 770, and light stabilizer 944. The anti-yellowing agent can be at least one of UDT, HN-130, SAS, and XHTS-011. The antioxidant can be at least one of antioxidant 1010, antioxidant 1035, antioxidant 1036, and antioxidant 1076. The bactericidal and mildew-proof agent can be at least one of BBIT, OIT, BIT, SPT, and DMDMH.

[0061] In combination with the first aspect, in some embodiments provided in the present application, the anti-hydrolysis agent includes at least one of monocarbodiimide and polycarbodiimide, and the anti-hydrolysis agent can inhibit hydrolysis and alleviate hydrolysis. The monocarbodiimide can be at least one of Stabaxol I, Eustab HS-700, and Hycasyl 100, and the polycarbodiimide can be at least one of StabaxolP, Stabaxol P100, and Stabilizer 9000.

[0062] In combination with the first aspect, in some embodiments provided in the present application, the filler includes at least one of calcium carbonate, kaolin, wollastonite powder, talc, mica powder, titanium dioxide, silica powder, alumina, aluminum hydroxide, barium sulfate and calcium sulfate. The role of the filler is to reduce the production cost of the product while improving the hardness or other properties such as flame retardancy, reinforcement, heat resistance, etc.

[0063] In combination with the first aspect, in some embodiments provided in the present application, the dehydrating agent includes at least one of activated molecular sieves, vinyltrimethoxysilane, and oxazolidine dehydrating agent. The function of the dehydrating agent is to remove moisture from the system, reduce the occurrence of side reactions, and extend the shelf life of the product.

[0064] In combination with the first aspect, in some embodiments provided in the present application, the thixotropic agent includes at least one of fumed silica and organic bentonite, and the functions of the thixotropic agent mainly include thickening thixotropy, reinforcement, anti-sagging and anti-settling functions. The thixotropic agent significantly improves the mechanical properties, construction convenience and storage stability of the adhesive through its unique physical and chemical properties.

[0065] In combination with the first aspect, in some embodiments provided in the present application, the plasticizer includes one or more of phthalic acid diesters, adipate diesters, sebacic acid diesters, and phosphate esters, specifically at least one of dioctyl phthalate, dibutyl phthalate, diisononyl phthalate, dimethyl adipate, dioctyl adipate, dibutyl sebacic acid, dioctyl sebacic acid, tricresyl phosphate and trioctyl phosphate. The function of the plasticizer is to adjust viscosity and fluidity, improve flexibility and ductility, increase adhesion and bonding strength, adjust hardness and temperature resistance, and improve brittleness and impact resistance.

[0066] In combination with the first aspect, in some embodiments provided in the present application, the isocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, p-phenylene diisocyanate, 1,4-cyclohexane diisocyanate, xylene diisocyanate, cyclohexane diisocyanate, trimethyl-1,6-hexamethylene diisocyanate and polymethylene polyphenyl polyisocyanate. The role of the isocyanate is to act as a curing agent, react with a hydroxyl group to form a carbamate, undergo a cross-linking reaction, and produce a cured product.

[0067] In combination with the first aspect, in some embodiments provided in the present application, the silane coupling agent includes at least one of γ-glycidyloxypropyltrimethoxysilane, methyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, anilinemethyltriethoxysilane, anilinepropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The role of the silane coupling agent is to enhance the wettability and substrate adhesion of the polyurethane adhesive.

[0068] In combination with the first aspect, in some embodiments provided in the present application, the viscosity of the isocyanate-terminated polyurethane prepolymer at 80° C. is 400 mPa·s to 1000 mPa·s. The viscosity of the isocyanate-terminated polyurethane prepolymer at 80° C. is within this range, which can have better fluidity and processing performance.

[0069] In combination with the first aspect, in some embodiments provided in the present application, the isocyanate-terminated polyurethane prepolymer is prepared by the following method:

[0070] The hydroxy-terminated polybutadiene and the first part of the plasticizer are mixed and dehydrated to obtain a first product;

[0071] The first product is mixed with isocyanate and a second portion of plasticizer to react to obtain an isocyanate-terminated polyurethane prepolymer.

[0072] By first mixing the hydroxy-terminated polybutadiene and the first part of the plasticizer, and then reacting with the isocyanate and the second part of the plasticizer after dehydration, the isocyanate-terminated polyurethane prepolymer is obtained, which can make the polyurethane prepolymer have a higher qualified rate. The plasticizer is added step by step, and the second part of the plasticizer can bring the isocyanate with a larger viscosity remaining in the feed pipe into the reactor, so that the product has a higher qualified rate. It should be noted that the plasticizer here is the plasticizer in component B.

[0073] In combination with the first aspect, in some embodiments provided in the present application, the mass ratio of the first part of the plasticizer to the second part of the plasticizer is (4-9):1. The mass ratio of the first part of the plasticizer to the second part of the plasticizer is within this range, which can reduce the impact of moisture in the second part of the plasticizer on the system.

[0074] In combination with the first aspect, in some embodiments provided in the present application, the water content of the first product is less than 500 ppm. The water content of the first product within this range can minimize the reaction of water in the system with NCO in the system.

[0075] In combination with the first aspect, in some embodiments provided herein, the reaction temperature for mixing the first product with isocyanate and the second part of the plasticizer is 70° C. to 90° C. The reaction temperature for mixing the first product with isocyanate and the second part of the plasticizer is within this range, which can reduce the occurrence of side reactions.

[0076] In combination with the first aspect, in some embodiments provided in the present application, component A further comprises a pigment, and the pigment comprises at least one of carbon black, iron black and aniline black. Adding the pigment can distinguish the two components A and B, and using the black pigment can highlight the glue line in the light-colored substrate or hide the glue line in the dark-colored substrate.

[0077] In conjunction with the first aspect, in some embodiments provided in the present application, in terms of mass fractions:

[0078] Component A includes:

[0079]

[0080]

[0081] Component B includes:

[0082]

[0083] When the mass fraction of each substance in component A is within this range, the role of each raw material can be brought into play and the designed performance can be achieved.

[0084] The mass fraction of each substance in component B is within this range, which can bring out the role of each raw material.

[0085] Achieve designed performance.

[0086] In a second aspect, the present application provides a method for using a two-component polyurethane adhesive, wherein component A and component B are mixed in a volume ratio of 1:1. Component A and component B are mixed in a volume ratio of 1:1 to bring into play the role of each raw material and achieve the designed performance.

[0087] The technical solution provided by the present application is described in detail below in conjunction with the examples. The A components of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1, the B components of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 2, the mass fractions of the A components of Examples 1 to 6 are shown in Table 3, and the mass fractions of the B components of Examples 1 to 6 are shown in Table 4.

[0088] Table 1 Composition of component A of Examples 1 to 6 and Comparative Examples 1 to 2

[0089]

[0090]

[0091] In component B, the raw material composition of prepolymer 1 of the isocyanate-terminated polyurethane prepolymer is 20 to 50 parts of hydroxyl-terminated polybutadiene, 10 to 20 parts of plasticizer and 20 to 50 parts of isocyanate. The raw material composition of prepolymer 2 of the isocyanate-terminated polyurethane prepolymer is 20 to 50 parts of hydroxyl-terminated polybutadiene, 20 to 40 parts of plasticizer and 20 to 50 parts of isocyanate.

[0092] Table 2 Composition of component B in Examples 1 to 6 and Comparative Examples 1 to 2

[0093]

[0094]

[0095] Table 3 Composition of component A in Examples 1 to 6 and Comparative Examples 1 to 2 by mass (unit: part)

[0096]

[0097] Table 4 Composition of component B in Examples 1 to 6 and Comparative Examples 1 to 2 by mass (unit: part)

[0098]

[0099] Performance Testing

[0100] The two-component polyurethane adhesive components A and B of Examples 1 to 6 and Comparative Examples 1 to 2 were mixed evenly in a volume ratio of 1:1, and then the performance test was performed. The bonding performance test was performed by bonding the first substrate PP (pre-flame treated) to the second substrate PP+LGF (glass fiber reinforced PP, pre-flame treated). After the curing was complete, the tensile shear strength test was performed. The shear sheet failure forms were cohesive failure or substrate failure. The specific test method and steps were in accordance with the provisions of GB / T 7124, and the substrate sheet butt thickness was 1.5mm. After curing for 7 days under 23±2℃ / 50±5%RH environment, the test was performed on a tensile machine at a speed of 20mm / min. The specific aging conditions were:

[0101] (1) 90℃ for 336h (high temperature aging);

[0102] (2) -40℃ for 336h (low temperature aging);

[0103] (3) Place in warm water at 40°C for 336 h (hydrolysis aging);

[0104] After the aging treatment, take it out and place it at room temperature for 24 hours, and then conduct tensile shear strength test.

[0105] The test results are shown in Table 5.

[0106] Table 5 Performance of two-component polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 2 (I)

[0107]

[0108] The two-component polyurethane adhesive component A and component B of Examples 1 to 6 and Comparative Examples 1 to 2 were mixed evenly at a volume ratio of 1:1, and then the performance test was performed. The components were directly coated on the substrate (ABS+PC, ABS, ASA) and pressed, and the substrate was not subjected to any pretreatment such as grinding, flame, plasma, primer and electrophoresis. After the substrate was completely cured, the tensile shear strength test was performed. The specific test results are shown in Table 6.

[0109] Table 6 Performance of two-component polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 2 (II)

[0110]

[0111] The two-component polyurethane adhesive component A and component B of Examples 1 to 6 and Comparative Examples 1 to 2 were mixed evenly in a volume ratio of 1:1, and then the performance test was performed. The components were directly coated on the substrate (ABS+PC, ABS, ASA) and pressed, and the substrate was not subjected to any pretreatment such as grinding, flame, plasma, primer and electrophoresis. After the substrate was completely cured, the following aging treatments were performed respectively. The specific aging conditions were:

[0112] (1) 90℃ for 336h;

[0113] (2) Place at -40°C for 336 hours;

[0114] (3) Place in warm water at 40°C for 336 hours;

[0115] After the aging treatment, the samples were taken out and placed at room temperature for 24 hours, and then subjected to tensile shear strength tests. The specific test results for condition (1) are shown in Table 7, condition (2) are shown in Table 8, and condition (3) are shown in Table 9:

[0116] Table 7 Performance of two-component polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 2 (III)

[0117]

[0118]

[0119] Table 8 Performance of two-component polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 2 (IV)

[0120]

[0121] Table 9 Performance of two-component polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 2 (V)

[0122]

[0123]

[0124] As can be seen from Tables 5 to 9, the solvent-free two-component polyurethane adhesive provided by the present application has a wide range of application and has good adhesion to different types of substrates. Specifically, for ASA, ABS, ABS / PC composite materials, ASA / PMMA composite materials, etc., no pretreatment such as grinding, flame, plasma, primer, electrophoresis, etc. is required, and direct bonding is possible; for low surface energy plastics and composite materials such as polyester, PP, modified PP, fiber-reinforced PP, PE, etc., good bonding effects can be achieved after surface treatment.

[0125] The adhesive has good mechanical properties, with a surface drying time of less than 20 minutes, a bulk strength greater than 3Mpa, a shear strength greater than 3Mpa, a cohesive failure mode, and an elongation at break greater than 80%, achieving a balance between high strength and high toughness.

[0126] It has excellent aging resistance. After aging at high temperature, warm water and low temperature, the bonding strength has not decreased significantly. The failure form is cohesive failure or substrate failure, and it has good reliability.

[0127] Comparative Example 1 has poor performance due to the lack of the first hydroxy compound, the anti-aging agent and the anti-hydrolysis agent.

[0128] Comparative Example 2 has poor performance due to the lack of the first hydroxy compound, the anti-aging agent and the anti-hydrolysis agent.

[0129] In summary, by setting up separately arranged component A and component B, the hydroxyl group in component A and the isocyanate group in component B undergo addition reaction during use, thereby achieving adhesion and improving bonding strength, while the polar groups in component A and component B can achieve reliable bonding with the substrate. Moreover, the open time is long, high temperature can be quickly cured, the body strength is large, the shear strength is large, and the elongation at break is high, achieving a balance between high strength and high toughness. At the same time, the two-component polyurethane adhesive of the present application does not contain solvent, reducing solvent residue.

[0130] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0131] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.

[0132] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A two-component polyurethane adhesive, characterized in that: It comprises a component A and a component B which are separately arranged, wherein: Component A includes: hydroxyl-containing compounds, chain extenders, catalysts, anti-aging agents, anti-hydrolysis agents, fillers, dehumidifiers and thixotropic agents; Component B includes: isocyanate-terminated polyurethane prepolymer, isocyanate, water scavenger, silane coupling agent, plasticizer, filler and thixotropic agent; The hydroxyl-containing compound includes hydroxyl-terminated polybutadiene and a first hydroxyl-containing compound.

2. The two-component polyurethane adhesive according to claim 1, characterized in that: The hydroxyl value of the hydroxy-terminated polybutadiene is 20 mg to 150 mg KOH / g; and / or, The number average molecular weight of the hydroxy-terminated polybutadiene is 1000-8000.

3. The two-component polyurethane adhesive according to claim 1, characterized in that: The molecular weight of the first hydroxyl-containing compound is 100-1000.

4. The two-component polyurethane adhesive according to claim 1, characterized in that: The first hydroxyl-containing compound includes at least one of diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, ethylene glycol tert-butyl ether, dodecanol, sorbitol, glycerol and 2-ethyl-1,3-hexanediol; and / or, The chain extender comprises at least one of ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, methylpropylene glycol, dipropylene glycol and trimethylolpropane; and / or, The catalyst comprises at least one of an organic metal compound and an amine compound; and / or, The anti-aging agent includes at least one of an ultraviolet absorber, a hindered amine light stabilizer, an anti-yellowing agent, an antioxidant and a bactericide and antifungal agent; and / or, The anti-hydrolysis agent comprises at least one of monocarbodiimide and polycarbodiimide; and / or, The filler comprises at least one of calcium carbonate, kaolin, wollastonite powder, talc, mica powder, titanium dioxide, silica powder, alumina, aluminum hydroxide, barium sulfate and calcium sulfate; and / or, The dehydrating agent comprises at least one of activated molecular sieve, vinyltrimethoxysilane and oxazolidine dehydrating agent; and / or, The thixotropic agent comprises at least one of fumed silica and organic bentonite; and / or, The plasticizer includes one or more of phthalic acid diesters, adipate diesters, sebacic acid diesters, and phosphate esters, specifically at least one of dioctyl phthalate, dibutyl phthalate, diisononyl phthalate, dimethyl adipate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, tricresyl phosphate, and trioctyl phosphate; and / or, The isocyanate comprises at least one of toluene diisocyanate, diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, p-phenylene diisocyanate, 1,4-cyclohexane diisocyanate, xylylene diisocyanate, cyclohexane dimethylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate and polymethylene polyphenyl polyisocyanate; and / or, The silane coupling agent includes at least one of γ-glycidyloxypropyltrimethoxysilane, methyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, anilinemethyltriethoxysilane, anilinepropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane.

5. The two-component polyurethane adhesive according to claim 1, characterized in that: The viscosity of the isocyanate-terminated polyurethane prepolymer at 80° C. is 400 mPa·s to 1000 mPa·s.

6. The two-component polyurethane adhesive according to claim 1, characterized in that: The isocyanate-terminated polyurethane prepolymer is prepared by the following method: The hydroxy-terminated polybutadiene and the first part of the plasticizer are mixed and dehydrated to obtain a first product; The first product is mixed with isocyanate and a second portion of plasticizer to react to obtain an isocyanate-terminated polyurethane prepolymer.

7. The two-component polyurethane adhesive according to claim 6, characterized in that: The mass ratio of the first part of plasticizer to the second part of plasticizer is (4-9):1; and / or, The first product has a water content of less than 500 ppm; and / or, The reaction temperature for mixing the first product with the isocyanate and the second portion of the plasticizer is 70°C to 90°C.

8. The two-component polyurethane adhesive according to claim 1, characterized in that: Component A further comprises a pigment, wherein the pigment comprises at least one of carbon black, iron black and aniline black.

9. The two-component polyurethane adhesive according to claim 8, characterized in that: In parts by mass: Component A includes: Component B includes:

10. A method for using the two-component polyurethane adhesive according to any one of claims 1 to 9, characterized in that: When in use, component A and component B are mixed in a volume ratio of 1:1.

Citation Information

Cited By

  • High-thermal-conductivity hydrolysis-resistant flame-retardant polyurethane pouring sealant and preparation method thereof

    CN120082318A

  • Thermoplastic wave-absorbing material as well as preparation method and application thereof

    CN121592162A